2020
DOI: 10.22159/ajpcr.2020.v13i8.37989
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, and Practices of Self-Medication Among the Students of Private University

Abstract: Objectives: Self-medication is becoming very common in our routine life which is an unhealthy and risky practice in a few instances. The present study was carried out to determine the knowledge, attitude, and practice of self-medication among students of Charotar University of Science and Technology (CHARUSAT). Methods: A pre-validated questionnaire was prepared and distributed among the students. Data was collected and analyzed using Microsoft Excel and the results expressed as counts and percentages.&#… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
3
2
0
Order By: Relevance
“…The study conducted by Ainsy Goldlin [28] concluded that main factors related to self-medication were COVID 19 spread and fatality, fear of going to hospitals, lack of trouble-free access to hospitals (39.6%), which was in accordance to our study. Another similarity of our study was with the study done by Chopra [29] and also by Jalpa [30] where self-medication was more common in women with 62% and 66%, respectively than in men.…”
Section: Discussionsupporting
confidence: 88%
“…The study conducted by Ainsy Goldlin [28] concluded that main factors related to self-medication were COVID 19 spread and fatality, fear of going to hospitals, lack of trouble-free access to hospitals (39.6%), which was in accordance to our study. Another similarity of our study was with the study done by Chopra [29] and also by Jalpa [30] where self-medication was more common in women with 62% and 66%, respectively than in men.…”
Section: Discussionsupporting
confidence: 88%
“…These findings are similar to that of studies in Pakistan and Nepal which also reported headache (69 to 73%) and common cold/flu (56 to 66%) as the most common minor ailments encountered by university students [6,7]. In addition, studies from Egypt and Mekelle indicated that headache (50 to 60%) and common cold (44 to 70%) were the most frequent reason for self-medication among university students [8,14,15].…”
Section: Discussionsupporting
confidence: 86%
“…In this study, knowledge of medicines through similar previous illnesses and the feeling that there is no need to consult for minor ailments were the main reasons for self-medication among both first and 2 nd -year medical undergraduates. This is in line with Suthar et al, in which the participants who were university students stated that there is "no need to visit the doctor for minor illness" [17]. Jagadeesh et al stated that self-medication creates awareness among individuals toward maintaining their health and hence need to be promoted amongst medical students [2].…”
Section: Discussionsupporting
confidence: 70%